ANALISIS PENGARUH JALAN TRANS PAPUA JAYAPURA-WAMENA TERHADAP SOSIAL-EKONOMI MASYARAKAT KABUPATEN YALIMO - Tetjuari, Kristanto Alexander; Julison, Bernathius; Rusim, Dewi Ana (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2023)
This study aims to provide an overview of the Trans Papua Jayapura-Waeman road construction project which is included as a Strategic Priority Project (Major Project) numbered 31 in Presidential Decree number 18 of 2020 concerning the National Medium Term Development Plan (RPJMN) 2020-2024. This road construction project contains plans for the construction of nine roads from Sorong to Merauke. The approach used in this study is a qualitative approach with the research subject being the local government of Yalimo Regency. The selected informants were those who had the relevance needed for research consisting of the Head of the Yalimo District Development Office, the Secretary, the Head of the Yalimo District Community Social Welfare Service as respondents. Data collection techniques using observation and interviews or interviews. The data were analyzed qualitatively descriptively supported by primary and secondary data. The results showed that the Trans Papua Jayapura-Waemana Road had a positive impact on the social and economic changes of the community in Yalimo Regency. Overall, it can be seen from 3 (three) aspects of research observations which include; Increasing Productive Economic Enterprises. The factors that affect the social and economic level of the community include; the availability of an adequate budget, There is a strong commitment from the government (Pemda) in supporting the implementation of development. Inhibiting factors include; Lack of facilities and infrastructure, the existence of community habits, and others (cultural factors).Â